When administration and corporate culture are not enough for school management: empirical evidence - Jiménez-Herrera, Julio (Emerging Trends in Education, 2022)
This research about sustainable development and its relationship with corporate culture was developed in a medium-sized city in the south of Mexico, Veracruz. The objective of this work is to find a comprehensive-interpretative explanation of the phenomenon studied to evidence the relationships that are established between the administrative discourse (management), the organizational culture and some elements of sustainable development. This research was developed under a qualitative modality and were used as techniques for the collection of information, individual and semi-structured interviews that were recorded and later transcribed for analysis. It presents the case of a school where despite de efforts made by the organizational actors (director, students, secretary, professors and parents) to make their school a sustainable organization, fundamental controversies are observed between what was planned and executed (administration), with he values, believes and the meanings that the actors give to the care of the resources inside the institution ( organizational culture) in terms of inhibit the waste of the electric energy, the water, and the non-assumption of the ecological habits to develop and maintain the green areas of the school. Keywords: Administration; Culture; Organization; Sustainable; School management